The Lion's Lady - Garwood, Julie (USA, 1993)
Castles: Orphaned and besieged, Princess Alesandra knows that only marriage to an Englishman can protect her from the turmoil in her own land. To the amusement of her makeshift guardian, Colin, younger brother of the Marquess of Cainewood, the raven-haired beauty instantly captivates London society. But when Alesandra is threatened by her unscrupulous countrymen, the fighting instinct that won Colin a knighthood are rekindled... The Lion's Lady: Christina Bennett had taken London society by storm. The ravishing beauty guarded the secret of her mysterious past until the night Lyon, Marquis of Lyonwood, stole a searching, sensuous kiss. An arrogant nobleman with a pirate's passions, he tasted the wildfire smoldering beneath Christina's cool charm and swore to possess her...
Keywords: Fiction; Historical; Romance